The Comparative Analysis of Financial Distress Precipitating Factors in Islamic Banking in Indonesia and Malaysia Based on Bankometer Variables - Amelia Pratiwi; Tri Verani; Asyarf Rayhan (Falah: Jurnal Ekonomi Syariah, 2023)
This study seeks to identify and compare descriptively the factors that influence the likelihood of financial distress in Indonesian and Malaysian Islamic banking. This study selected some variables and standard ratio values based on the Bankometer model such as Islamic banks’ capital adequacy, leverage level, credit risk, efficiency, and liquidity. The financial ratio data collected from published financial reports from five Indonesian Islamic banks and four Malaysian Islamic banks then analyzed using binary logistic regression. The results indicate that during the observation periods, the capital level (CA and CAR), leverage level (EA), and credit risk (NPF) of Islamic banking in Indonesia and Malaysia met the Bankometer standard. Meanwhile, the liquidity level (LA) of Islamic banks in both countries slightly exceeded the Bankometer's maximum standard, especially before the pandemic period. The findings in this study may enrich the discourse on the factors that trigger possible financial distress in Islamic banking by collaborating with the Bankometer model and binary logistic regression.